Immature recall ability in dream reporting with children aged 3-5 - Gartner, Yvonne (Department of Psychology, 2015)
The content of dreams of children aged between three and five years old has been the topic of ongoing debate in past dream research. The bulk of this research was conducted by Foulkes (1982, 1999), who concluded that children of this age group experience impoverished dreams with little emotional content, an absence of active self-participation, and a lack of kinematic imagery (i.e., mental representations of movement, activities and interactions). These conclusions were based on the brief and mundane dream reports provided by children during his 1982 longitudinal laboratory study. However, Foulkes’ research did not test the children’s memory skills and ability to narrate an event, and did not compare these to the dream reports the children produced. The importance of memory skills and narrative ability as potential confounds when studying children’s dreams has been postulated in existing literature. In view of the findings of past studies on young children’s dreams and their cognitive capacity for dreaming, the present study re-examined the quantitative and qualitative features of dream reports of children aged three to five years old. The present study included parameters of testing memory skills and narrative ability to analyse whether these confound the dream report findings, and if so, whether one can draw any firm conclusions about dreams based on a dream report provided by the children.